Investigation of potato starch and sonicated RAS as alternative carbon sources for biological nitrogen removal. (8th June 2009) - Kuncoro, Gideon; Ngothai, Yung; Kaeding, Uwe; Sweeney, David; , Brian O'Neill
High nitrogen discharge from wastewater impacts negatively on the marine environment. Under the South Australian Environmental Improvement Program, metropolitan wastewater treatment plants are reconfigured to meet the new nitrogen discharge guideline. The denitrification process is carbon limited with carbon supplementation required to meet discharge guidelines, hence molasses is used for carbon source. Although molasses is inexpensive, other carbon sources particularly industrial waste potato starch and sonicated Return Activated Sludge (RAS) are explored. Research to evaluate soluble carbon release is quantified and preliminary results are presented suggesting that sonicated RAS may be an attractive substitute for molasses.